Methemoglobinemia – Two Uncommon Presentations - Gundogdu, Zuhal; Ipekçi, Belkıs; Çınar , Bengu (IIUM Medical Journal Malaysia, 2018)
Two rather different cases of methemoglobinemia are presented. The first case is an infant who had a circumcision procedure with prilocaine. The second case involves a 14-year-old girl who attempted suicide with an overdose of metoclopramide and butamirate citrate. The attention is drawn to differences in hospital admission and management especially with respect to methemoglobin level and age. If methemoglobin levels reach ≥ 10%, cyanosis would appear first. Symptoms of hypoxemia and diminished oxygen transport do not develop until levels reach 30 to 40%. Not only early intervention is crucial but also patients should not be discharged from the hospital too soon. Doctors should be able to identify high risk patients, paying a special attention to infants younger than three months old who might be at an increased risk of methemoglobinemia which is a potentially lethal complication of prilocaine. As for our second case, methemoglobin level has not increased, despite an overdose of metoclopramide. This may be due to age or timely elimination of toxic agents by gastric lavage, catharsis and administration of procyclidine.